Pengaruh pH dan Konsentrasi Terhadapa Penyerapan Ion Logam Besi (Fe) Menggunakan Selulosa Hasil Ekstraksi Dari Kulit Durian (Durio Zibethinus Murr) - Burma, Resna; Nasra, Edi; Oktavia, Budhi; Ningsih, Sherly Kasuma Warda (Departemen Kimia FMIPA UNP, 2024)
Fe(II) Metal Ions are one type of heavy metal that is toxic resulting in pollution in the environment. In waters if Fe(II) ion exceeds the limit of 0.3 mg / L will cause damage to the ecosystem and the surrounding environment, so countermeasures are needed from pollution caused by Fe(II) ions. Biosorption using cellulose biosorbents extracted from durian fruit peel was chosen as one of the efficient methods. The purpose of this study can determine the absorption capacity of durian fruit peel and determine the optimum conditions for absorption of Fe (II) metal ions carried out by batch method with variations in pH and concentration. The optimum pH of Fe (II) metal ion absorption was obtained at pH 5 and an optimum concentration of 250 ppm with an absorption capacity of 4.3 mg / g.